Frankfurt's Unwilling and Willing Addicts. Issue 503 (11th April 2017) - Sripada, Chandra
Abstract: Harry Frankfurt's Unwilling Addict and Willing Addict cases accomplish something fairly unique: they pull apart the predictions of control-based views of moral responsibility and competing self-expression views (a type of deep self view). The addicts both lack control over their actions but differ in terms of expression of their respective selves. Frankfurt's own view is that—in line with the predictions of self-expression views—the unwilling addict is not morally responsible for his drug-directed actions while the willing addict is. But is Frankfurt right? In this essay, I put together a systematic defence of Frankfurt's position.